Mechanizmy lékové rezistence a nádorové kmenové buňky - Holčaková, J; Nekulová, M; Orzol, P; Vojtěšek, B (Klinicka onkologie, 2014)
Although the success of anticancer treatments has been increasing annually, drug resistance remains the dominant cause of death of cancer patients. Initial therapy often leaves residual dis-ease that leads to repeated tumor development or to loss of its sensitivity to available therapy. One reason of residual disease formation is the presence of cancer stem cells (CSCs). CSCs have been identified as a small population of cells that is capable of self renewal and differentiation. It is supposed that these cells are responsible for cancer initiation, progression, metastasis, recurrence and drug resistance. Over the past years, much attention has been paid to development of CSCs related therapies and to identification of key molecules involved in controlling the specific properties of CSCs populations. This article reviews the basic mechanisms of drug resistance in relation to cancer stem cells.
Keywords: nádory; chemorezistence; Drug Resistance, Neoplasm; nádorové kmenové buňky; lidé; Neoplasms; Neoplastic Stem Cells; Humans